Organic amendments effect on the soil chemical properties of marginal land and soybean yield - Ulfa Mutammimah; Slamet Minardi; Suryono Suryono (Brawijaya University, 2020)
Land use change is increasing, causing a lack of optimal land for agriculture. Marginal land improvement can be made with the application of organic amendments that can improve soil fertility to be optimal for crop cultivation. Land-use change is increasing, causing a lack of optimal land for agriculture. Marginal land improvement can be made with the application of organic amendments that can improve soil fertility to be optimal for crop cultivation. This study was carried out on acid soil of Karanganyar Regency. The treatments tested were P0 (control), P1 (2.5 t rock phosphate/ha + 5 t cow manure/ha), P2 (5 t rock phosphate/ha + 5 t cow manure /ha), P3 (2.5 t dolomite/ha + 5 t cow manure /ha), P4 (5 t dolomite/ha + 5 t cow manure/ha), P5 (5 t rock phosphate/ha + 5 t dolomite/ha + 5 t cow manure/ha) . The result showed that the application of P5 gave the highest yield of soybean of 1.41 t/ha. The application of manure significantly affected soil chemical properties of available P, available Ca, organic matter, and cation exchange capacity, but it did not significantly affect total N.